504 Aetiology and Electrocardiogram Findings in Children Presenting to the Emergency Department with Chest Pain. (October 2012) - Tan, RHK; Saravanan, R; Ladusans, E; Ryan, M
Abstract : Introduction: Chest pain is a frequent cause of attendance to the emergency department. Electrocardiogram (ECG) is often used as a first line investigation. This study aims to investigate the aetiology of chest pain and usefulness of ECG in a group of 200 children ranging between 3–16 years who presented between June - December 2009. Methods: ED casenotes were reviewed retrospectively to study the demographic features, clinical characteristics, ECG utilization and final diagnoses of these children. Children were placed in two groups. The first group were those who had suggestive history (crushing/exertional pain/palpitations), positive examination findings, or previous cardiac/family history. The second group of patients consisted of those without these features. Results: Musculoskeletal chest pain (46%) is the most common diagnosis in children followed by respiratory (15%), gastrointestinal (14%), idiopathic (13%), and psychological (7.5%) causes. Cardiac cause chest pain (4.5%) was the least common. Only 20 patients (10%) presented with positive cardiac features according to the criteria used. 81 (40.5%) patients in total had an ECG performed. Of the 20 patients with cardiac features, 15 (75%) had an ECG compared to 66 (37%) patients in the other group. (p<0.0014) Four abnormal ECGs were obtained. These were all from the group with positive cardiac features. (p<0.0008). Conclusion: Musculoskeletal pain was found to be the most common cause of chest pain. Electrocardiogram has poor yield when performed in children without significant cardiac history/examination findings. However, it remains a useful screening tool and is beneficial for reassurance of patients and their families.